An Analysis of Phonological, Morphological, and Semantic Development in a Five-Year-Old Child’s Spoken Language - Ainun Aghniya; Hilma Safitri; Farah Adelia Dewinta; Starla Putri Nabila (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze early childhood language development through three linguistic aspects: phonology, morphology, and semantics. The data was collected from the utterances of a young child during natural interactions. A descriptive qualitative method was used, focusing on observation and documentation of spontaneous speech. The findings reveal that children at an early age undergo various phonological simplifications, morphological constructions, and semantic categorization based on their everyday experiences. Phonological errors such as sound substitution and reduction were frequently observed. Morphological patterns such as reduplication and affixation show an early awareness of word formation. In the semantic domain, the child demonstrated understanding of categories such as objects, people, and actions. This study highlights the natural progression of linguistic abilities in children, emphasizing the developmental patterns in acquiring language.